Oscilador de Dirac: cenário para um estudo de um sistema de dois níveis - Pinheiro, Hudson Pacheco (2009)
In this dissertation, we studied how the Dirac oscillator model behaves when interacting with external electromagnetic field inside os a two-level system and without considering the field quantization (semiclassical theory). In order to do it, we obtained the population inversion function of energy and spin in three situations: without Lorentz-breaking symetry terms; with the introduction of CPT-odd terms which broke the Lorentz vetorial symmetry, vµ ¯ ψγµψ; with the introduction of CPT-odd terms which broke the Lorentz symmetry by the axial coupling, bµ ¯ ψγ5γµψ. Then, we analised the special case of ressonance between the system and the field of incidence. In this case, all influence from the Dirac oscillator was lost and the population inversion function of the energy and spin became the same as the one found in scientific literature.